Sustainable IT and Green Computing: A Qualitative Study on Eco-Friendly Practices in Tech Companies - Multi Nadeak; Adi Widodo; Manorang Sihotang (Journal of Information Systems and Management (JISMA), 2026)
Environmental concerns and the urgent need for sustainable development have driven technology companies to adopt green computing practices. This qualitative study explores the motivations, barriers, and strategies employed by technology companies in implementing sustainable information technology (IT) practices. Through semi-structured interviews with 22 sustainability managers, IT directors, and environmental officers from multinational tech companies, we identified key themes including renewable energy adoption, electronic waste management, energy efficiency optimization, and stakeholder engagement. The findings reveal that while companies recognize the business case for sustainability, implementation challenges persist, particularly regarding supply chain complexity, technological constraints, and financial investment requirements (Jafari et al., 2024). Our study contributes valuable insights into how tech companies navigate the transition to green computing, offering practical recommendations for practitioners and policymakers. The research emphasizes the critical importance of integrated sustainability strategies, organizational commitment, and collaborative ecosystem approaches in achieving meaningful environmental outcomes in the technology sector.